Development of Peer-Based Academic Supervision Model in Increase Skills Teaching The 21st Century in Elementary Schools - Retno Pramasari; Bambang Ismanto; Sophia Tri Satyawati; Ji Suk Young; Ester Uru Hida (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study aims to develop a peer-based academic supervision model to enhance 21st-century teaching skills in elementary schools. The research employs a Research and Development (R&D) approach based on the Borg & Gall model, utilizing a mixed-method design with a Sequential Exploratory Design. The research subjects consist of teachers from SD Negeri Banyubiru 01, Semarang Regency, Central Java Province. Data were collected through observations, interviews, questionnaires, and documentation, which were subsequently analyzed using both qualitative and quantitative approaches. Product validation involved two experts (content and language). Qualitative data validation applied source triangulation and technique triangulation, while quantitative data validation employed expert judgment. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were processed using the Mann-Whitney statistical test. Expert validation resulted in an average score of 90% (categorized as highly feasible) for content and 93% (highly feasible) for language. The findings indicate that the peer-based academic supervision model positively impacts teachers' teaching skills, as evidenced by the Mann-Whitney test results, which reveal a significant difference in teachers' pedagogical competence before and after the implementation of academic supervision. Through this approach, teachers can exchange experiences, provide constructive feedback, and enhance their professional teaching practices. Moreover, the model fosters a collaborative school culture and encourages innovation in teaching methods. The peer-based academic supervision model has proven effective in improving teachers’ teaching skills in the context of 21st-century education. Therefore, this model is recommended for broader implementation with policy support from schools and educational authorities to sustainably enhance the quality of teaching and learning.